Assessment of an energy-efficient aircraft concept from a techno-economic perspective - Goldberg, Chana; Nalianda, Devaiah; Sethi, Vishal; Pilidis, Pericles; Singh, Riti; Kyprianidis, Konstantinos (Elsevier, 2018)
An increase in environmental awareness in both the aviation industry and the wider global setting has led to large bodies of research dedicated to developing more sustainable technology with a lower environmental impact and lower energy usage. The goal of reducing environmental impact has necessitated research into revolutionary new technologies that have the potential to be significantly more energy efficient than their predecessors. However, for innovative technologies in any industry, there is a risk that adoption will be prohibitively expensive for commercial application. It is therefore important to model the economic factors of the new technology or policy at an early stage of development. This research demonstrates the application of a Techno-economic Environmental Risk Assessment framework that may be used to identify the economic impact of an energy-efficient aircraft concept and the impact that environmental policy would have on the viability of the concept. The framework has been applied to a case study aircraft designed to achieve an energy saving of 60% in comparison to a baseline 2005 entry-into-service aircraft. The model compares the green aircraft concept to a baseline conventional aircraft using a sensitivity analysis of the aircraft direct operating cost to changes in acquisition and maintenance cost. The research illustrates an economically viable region for the technology. Cost margins are identified where the increase in operating cost due to expensive novel technology is counterbalanced by the reduction in cost resulting from low energy consumption. Viability was found to be closely linked to fuel price, with a low fuel price limiting the viability of energy-efficient aviation technology. In contrast, a change in environmental taxation policy was found to be beneficial, with the introduction of carbon taxation incentivising the use of an environmentally optimised aircraft.
Keywords: Techno-economics; Green aviation; Alternative fuels